TINGKAT KEBAHAGIAAN PADA MAHASISWA FAKULTAS KESEHATAN MASYARAKAT UNIVERSITAS AIRLANGGA PSDKU BANYUWANGI: Level of Happiness in Students of Public Health Universitas Airlangga PSDKU Banyuwangi - Yuniar Amalia; Ayik Mandagi (Lembaga Penelitian dan Terapan untuk Kesehatan Jiwa (Lenterakaji), 2019)
ABSTRACT Happiness is something very desirable for every human being. They tend to want a quiet, comfortable life and make them feel safe. This study aims to determine the level of happiness of public health faculty students at Airlangga University PSDKU Banyuwangi. This study uses a quantitative descriptive approach with the type of survey research. The sample in this study were 43 students of the Faculty of Public Health. The sampling technique in this study using simple random sampling technique. The instrument in data collection uses a happiness level scale that is modified from the Subjective Happiness Scale and Satisfaction with Life Scale. Statistical analysis techniques use non parametric. The results of the study showed that happiness in the Faculty of Public Health students was in the moderate category